PENGEMBANGAN INSTRUMEN PENILAIAN DIRI PADA SISWA TATA BUSANA DI YOGYAKARTA - Mahanani, Chytra; Susanto, Moh. Rusnoto; Mahanani, Thyara (Prosiding Pendidikan Teknik Boga Busana, 2021)
am study; 2) Knowing the consistency of the assessment between the student’s self-assessment and the lecturer’s assessment of making shirts for Fashion students. This research is a research and development (R&D), using a 4D development model (Define, Design, Develpoment, Disseminate). The population of this research is Fashion program study Clothing students. The research sample as a source of information is Fashion Students with clothing concentration. The sampling technique uses purposive sampling. The data collection method uses the assessment tools, in the form of assessment sheets, rubrics, procedures and how to determine the final score. The validity of the instrument uses content validity based on judgment-expert, namely experts in clothing and measurement. While the reliability test uses inter-rater from Kappa 0.87.> The index of 0.81 meets good instruments. The consistency of the assessment of lecturers and students is 0.66> 0.61, which means that the assessment has been included in the consistent category. Outcomes of planned research targets are Proceedings at the UNY National Seminar Keywords: Instrument of Assessment, Men’s Shirts, Research and Development